Vigorous but Short-Term Gamma Interferon T-Cell Responses against a Dominant HLA-A*02-Restricted Measles Virus Epitope in Patients with Measles - Jaye, Assan (American Society for Microbiology, 2003)
The absolute and relative abundance of major histocompatibility complex class I-presented viral epitopes is important in the induction and maintenance of antiviral cytotoxic-T-lymphocyte (CTL) responses. We demonstrate that the supra-abundant HLA-A*0201-restricted peptide KLWESPQEI of the measles virus nonstructural C protein induces strong gamma interferon CD8(+)-T-cell responses in children with acute measles. However, longitudinal analysis indicates that these responses are only short-lived. Thus, some viral epitopes that can be immunodominant during primary infection may fail to establish memory CTL responses.